Freeboard life-cycle benefit-cost analysis of a rental single-family residence for landlord, tenant, and insurer - Gnan, Ehab; Mostafiz, Rubayet Bin; Rahim, Md Adilur; Friedland, Carol J.; Rohli, Robert V.; Taghinezhad, Arash; Al Assi, Ayat (Frontiers in Climate, 2024)
Flood risk to single-family rental housing remains poorly understood, leaving a large and increasing population underinformed to protect themselves, including regarding insurance. This research introduces a life-cycle benefit-cost analysis for the landlord, tenant, and insurer (i.e., National Flood Insurance Program (NFIP)) to optimize freeboard (i.e., additional first-floor height above the base flood elevation (BFE)) selection for a rental single-family home. Flood insurance premium; apportioned flood risk among the landlord, tenant, and NFIP by insurance coverage and deductible; rental loss; moving and displacement costs; freeboard construction cost; and rent increase upon freeboard implementation are considered in estimating net benefit (NB) by freeboard. For a 2,500 square-foot case study home in Metairie, Louisiana, a two-foot freeboard optimizes the combined savings for landlord and tenant, with joint life-cycle NB of $23,658 and $14,978, for a 3% and 7% real discount rate, respectively. Any freeboard up to 2.5 feet benefits the tenant and NFIP, while the landlord benefits for freeboards up to 4.0 feet. Collectively, results suggest that at the time of construction, even minimal freeboard provides substantial savings for the landlord, tenant, and NFIP. The research provides actionable information, supporting the decision-making process for landlords, tenants, and others, thereby enhancing investment and occupation decisions.